Pengaruh Struktur Modal, Likuiditas, Pertumbuhan Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan (Studi kasus pada Perusahaan Pertambangan Subsektor Batubara yang terdaftar di BEI) - Ayu Kriwidianingsih; Prasetyo Nugroho (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study was to examine the influence of variable capital structure, liquidity, company growth and profitability on firm value.The population in this study were all coal mining companies listed on the Indonesia Stock Exchange in 2015-2019, totaling 23 companies. The sampling technique in this research is purposive sampling, so that the samples obtained in the study are 21 companies that are members of the coal sub-sector in 2015-2019. The data analysis technique is using classical assumption test and multiple linear regression analysis with the help of SPSS 16 for Windows application. The results of this study indicate that: Capital Structure, Liquidity, and company growth have a positive and not significant effect on firm value, while Profitability has a negative and significant effect on firm value in the mining sub-sector. coal listed on the Indonesia Stock Exchange 2015-2019.